2013
DOI: 10.1111/epp.12050
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐parasitic nematodes of potential phytosanitary importance, their main hosts and reported yield losses

Abstract: The potential phytosanitary importance of all named plant‐parasitic nematode species was determined by evaluating available information on species characteristics, association with economically‐important crop hosts, and ability to act as vectors of viruses or form disease complexes with other pathogens. Most named species of plant‐parasitic nematodes (PPN) are poorly known, recorded from a single location only, not associated with economically‐important crops, and not known to be associated with other plant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 306 publications
(218 reference statements)
1
57
0
2
Order By: Relevance
“…is commonly associated with the PPN community of tomato production systems and is endemic to soils in the traditional tomato producing regions in South Africa (Marais and Buckley, 1993;Marais and Swart, 2002). However, the economic impact of this nematode on tomato production is uncertain (Singh et al, 2013). Pure culture studies indicated that it caused tomato yield reduction at high densities, but had no effect at low densities (Tebenkova, 1987).…”
Section: Helicotylenchus Spp As Soil Health Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…is commonly associated with the PPN community of tomato production systems and is endemic to soils in the traditional tomato producing regions in South Africa (Marais and Buckley, 1993;Marais and Swart, 2002). However, the economic impact of this nematode on tomato production is uncertain (Singh et al, 2013). Pure culture studies indicated that it caused tomato yield reduction at high densities, but had no effect at low densities (Tebenkova, 1987).…”
Section: Helicotylenchus Spp As Soil Health Indicatormentioning
confidence: 99%
“…Although the economic or agronomic impact of Paratrichodorus spp. infestations on tomatoes have been noted, it is not well described in literature or given only local importance (Anwar, 1994;Greco and Di Vito, 2011;Singh et al, 2013). It is often a component of PPN communities associated with tomatoes.…”
Section: Paratrichodorus Spp: a 'New' Threat To Tomato Producers?mentioning
confidence: 99%
“…This genus is also rich in species, as for example Peneva et al (2013) listed 158 valid species and several others were described after this paper. Some of these species are of economic importance as pests as well as vectors of plant nepoviruses (Singh et al, 2013). L. distinctus Lamberti, Choleva and Agostinelli, 1983 was originally described from Bulgaria and subsequently recorded from some other countries of the Balkan Peninsula (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In chapter 2, I briefly reflected on the plant legacy effects on numbers of plant-parasitic nematodes. Plant-parasitic nematodes can cause considerable damage to crops (Singh, Hodda & Ash 2013), and control succession of vegetation (van der Putten, van Dijk & Troelstra 1988). Numbers of plant-parasitic nematodes increased with shoot biomass (chapter 2), but the shoot biomass in mixtures of R. sativus and V. sativa did not lead to a similar increase in plant-parasitic nematode abundances.…”
Section: Plant Legacy Effects On Other Soil Organismsmentioning
confidence: 99%
“…Although growing plants stimulate plant-feeding nematodes, careful selection of cover crop species can reduce specific nematode species (Thoden, Korthals & Termorshuizen 2011;Fourie et al 2016), and reduce yield losses in subsequent crops (Singh, Hodda & Ash 2013). Traditionally both nutrient cycling and pathogen suppression feedback pathways have been studied in isolation.…”
Section: Introductionmentioning
confidence: 99%